German Economic Review (De Gruyter, 2000)
German Economic Review (GER), the official publication of the German Economic Association (Verein für Socialpolitik), is an international journal publishing original and rigorous research of general interest in a broad range of economic disciplines. The scope of research approaches includes theoretical, empirical and experimental work.